Learning about fiscal policy and the effects of policy uncertainty - Josef Hollmayr; Christian Matthes (Deutsche Bundesbank, 2013)
The recent crisis in the United States has often been associated with substantial amounts of policy uncertainty. In this paper we ask how uncertainty about fiscal policy affects the impact of fiscal policy changes on the economy when the government tries to counteract a deep recession. The agents in our model act as econometricians by estimating the policy rules for the different fiscal policy instruments, which include distortionary tax rates. Comparing the outcomes in our model to those under full-information rational expectations, we find that assuming that agents are not instantaneously aware of the new fiscal policy regime (or policy rule) in place leads to substantially more volatility in the short run and persistent differences in average outcomes.
Keywords: E32; D83; E62; 330; DSGE; Fiscal Policy; Learning